2015
DOI: 10.1371/journal.pone.0141595
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status among Young Children Aged 1–3 Years: A Cross-Sectional Study in Wuxi, China

Abstract: BackgroundThe increasingly recognized importance of vitamin D has been discussed and vitamin D status among young children has attracted widespread attention in recent years. However, study on vitamin D status in young children aged 1–3 y is limited in China.ObjectiveTo evaluate the nutritional vitamin D status of young children aged 1–3 y in Wuxi, southeastern China.MethodsA large cohort of 5,571 young children aged 1–3 y were recruited in this study who visited the child health clinics at the Wuxi Maternity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 33 publications
3
37
2
2
Order By: Relevance
“…The cohort presented in the current study is much larger than these previous studies and included infants with different feeding patterns, and the blood sampling was across the calendar year. A large population‐based study performed in Wuxi, China (32°N; Zhao et al, ) reported serum 25OHD concentrations in 3,845 1‐year‐old children with median (IQR) of 74.7 (56.4, 94.3) nmol/L. Our study found the M ± SD 25OHD was 82.9 ± 24.9 nmol/L and median (IQR) 25OHD was 80.8 (67.5, 95.7) nmol/L in 6‐month‐old infants.…”
Section: Discussionsupporting
confidence: 47%
“…The cohort presented in the current study is much larger than these previous studies and included infants with different feeding patterns, and the blood sampling was across the calendar year. A large population‐based study performed in Wuxi, China (32°N; Zhao et al, ) reported serum 25OHD concentrations in 3,845 1‐year‐old children with median (IQR) of 74.7 (56.4, 94.3) nmol/L. Our study found the M ± SD 25OHD was 82.9 ± 24.9 nmol/L and median (IQR) 25OHD was 80.8 (67.5, 95.7) nmol/L in 6‐month‐old infants.…”
Section: Discussionsupporting
confidence: 47%
“…It can supply our body's required vitamin D by exposing daily to sunlight with uncovered skin of face, arms, back and legs for at least 5 to 30 minutes between 10 am and 3 pm. Currently, food sources and vitamin D supplements are very important for us due to lifestyle changes, air pollution and decreases in duration of sunlight exposure (2,(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency (VDD) has become a public health issue both in developed and developing countries [4-6]. It is estimated that more than 1 billion people have suffered from VDD [7]. VDD causes a variety of disorders that include but are not limited to calcium and phosphorus metabolism disorder, infection, autoimmune disease, tumours and allergic disease [8-10].…”
Section: Introductionmentioning
confidence: 99%